2021
DOI: 10.33448/rsd-v10i3.13204
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and biomechanical response time in patrol horses submitted to functional training

Abstract: Physical activities frequency and intensity performed by equine, athletes or workers, have been growing significantly enabling appearance of musculoskeletal disorders. Thus, the objective of this research was to evaluate the effect of a functional training program to measure short-, medium- and long-term response on epaxial musculature development, as well in linear kinematics of patrol horses. Eight 14±3.5 years-old horses, weighing 418±50 kg, were evaluated over a 90 days period to divided in short (30 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Thus, this increase in tension occurred as a result of the increased action of the abdominal muscles, which were recruited as a consequence of the imbalance generated by the dynamic lateral mobilization exercises, as well as by the activation of the epaxial muscles, which intensified the flexion and dorsal displacement of the spine. This explanation is based on the numerous studies that have identified hypertrophy of the epaxial musculature, Musculus multifidus, in horses submitted to dynamic mobilization exercises (Stubbs et al, 2011, Tabor, 2015, Oliveira et al, 2015, Rodrigues et. al., 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this increase in tension occurred as a result of the increased action of the abdominal muscles, which were recruited as a consequence of the imbalance generated by the dynamic lateral mobilization exercises, as well as by the activation of the epaxial muscles, which intensified the flexion and dorsal displacement of the spine. This explanation is based on the numerous studies that have identified hypertrophy of the epaxial musculature, Musculus multifidus, in horses submitted to dynamic mobilization exercises (Stubbs et al, 2011, Tabor, 2015, Oliveira et al, 2015, Rodrigues et. al., 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a large number of muscles are recruited, including the abdominal, epaxial, pelvic, propulsor, and pectoral Research, Society andDevelopment, v. 11, n. 17, e70111738409, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i17.38409 3 muscles (Oliveira et al, 2019). This group of exercises increases joint range of motion and strengthens the muscles in which the exercise is associated (Clayton et al, 2012;Rodrigues et al, 2021). Despite published research using dynamic mobilization exercises in horses, none has investigated the kinematics of the axial segment.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic use of DMEs have been shown to increase the crosssectional area (CSA) and restore symmetry of the m. multifidus spinae [6][7][8][9], increase the CSA of m. longissimus dorsi [6] and enhance overall posture [10]. M. multifidus atrophy has been associated with back pathologies [11] and chronic limb lameness [12], and typically does not recover spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, techniques that promote musculature strengthening in horses, such as functional exercises practice, have been extensively studied in recent years (RODRIGUES et al, 2021;, since they deal with non-invasive procedures aiming to prevent and Ciência Rural, v.52, n.2, 2022. Rodrigues et al rehabilitate horses, in cases of skeletal muscle injuries (OLIVEIRA et al, 2015;CLAYTON, 2016), promote muscle hypertrophy (D 'ANGELIS et al, 2005;STUBBS et al ., 2011;TABOR, 2015) and improve gait quality and athletic performance (CLAYTON et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Functional exercises practice is based on a targeted exercise set execution, using the animal's own body, in order to stimulate and strengthen several muscle groups; developing animal balance, motor coordination, elasticity, strength and concentration (OLIVEIRA et al, 2015). In addition, due to its ability to reduce muscle tension, functional exercises can also promote animal relaxation and; consequently, improve well-being (CLAYTON et al, 2010;RODRIGUES et al, 2021).…”
Section: Introductionmentioning
confidence: 99%